PROGRAM INTERVENSI DINI PADA KELUARGA YANG MEMILIKI ANAK AUTISME DENGAN HAMBATAN KOMUNIKASI VERBAL - Mutahara. B, Nurul (2015)
Penelitianinidilatarbelakangiolehmasihkurangnyaketerlibatan orang tuadalamlayananpendidikanbagianakberkebutuhankhusus.Hal iniberdampakpadakemampuankeluargadalammemberikanlayananintervensidini di rumah.Untukmengatasihaltersebut, keluargamembutuhkanrumusan program intervensidini yang akanmenjadipedomanbagikeluargadalammelaksanakanintevensikepadaanak. Tujuandaripenelitianiniadalahuntukmemperoleh data tentangkondisiobjektifanakdankeluarga yang memilikianakautismedenganhambatankomunikasi verbal, merumuskan program intervensidini yang akanmenjadipedomanbagikeluargadalammelaksanakanintervensi. Penelitianinimenggunakanpendekatankualitatifdenganmetodedeskriptif.Subjekpenelitian yang dipilihadalahsalahsatukeluarga yang memilikianakautismedenganhambatankomunikasi verbal di kota Makassar. Teknikpengumpulan data yang digunakanadalahobservasi, wawancaradanstudidokumentasi.Teknikanalisis data penelitianyaitureduksi data, display data, penarikankesimpulandanverifikasi.Hasilpenelitianmenunjukkanbahwa 1) Anakmengalamihambatankomunikasi verbal yang pencapaianperkembangankomunikasinyasetaradengananakusia 2-3 tahunsebagaidampakdarikondisiautisme yang dialami. 2) Kurangnyapemahamankeluargatentanghambatankomunikasianaksertacaramemberikanlayananintervensidini di rumah. 3) Rumusan program intervensidiniberdasarkankondisiobjektifsertakebutuhananakdankeluargadan4) Keluargadapatmelaksanakan program intervensidini. Hasilpenelitianinidirekomendasikankepada Orang Tua, Guru danSekolah. Kata Kunci: Program IntervensiDini, HambatanKomunikasi, AnakAutismedanKeluarga This research was conducted based on the lack of parents' involvement in education service for the children with special need. This kind of problem is impacted to the ability of a family to give the early intervention service in the house. To solve this problem, the family needs an early intervention program formula that becomes the guidance for the family in implementing the early intervention program towards the children. The purpose of this research is to gain the data about the objective condition of children and the family who have children with autism with verbal communication barrier, to formulate the early intervention program that becomes the guidance for the family in implementing the intervention program. The method used in this research was descriptive qualitative. The subject taken was a family who has children with autism with verbal communication barrier in Makassar. The technique of data collection used in this research was observation, interview and documentation. The technique of data analyses was data reduction, data display, conclusion and verification. The result of this research showed that 1) The child has the verbal communication barrier with level of communication development equals to 2-3 years old children as the impact of autism condition. 2) The lack of family comprehension about the children communication barrier as well as how to give the early intervention service in the house. 3) The early intervention program formulation is based on children and family objective condition and needs, and 4) the family can conduct the early intervention program. The result of this research is highly recommended to the parents, teachers and schools. Keywords :Early Intervention Program, Communication Barrier, Autism children, and Family